Segurança de pedestres em rotatórias urbanas - Souza, Johnny Vieira de (Universidade Federal de São Carlos, 2015)
The Traffic and Transport Engineering has developed several techniques to mitigate the pernicious causes from the risks associated with intersections or crossing points level in traffic. Among the several devices of better efficiency and lower cost are the roundabouts, which are intended to simplify the intersection, so that the traffic that interacts there has a safe conduct, with few points of conflict and small delays. Although today has been widely used in the world and brazilian urban traffic the roundabouts are geometric elements that prioritize or monopolize motorized vehicular traffic due to lack of infrastructure, whether by choice or lack of technical knowledge, for cyclists, pedestrians and public transport have equal security. To assess what are the indicators that lead to this monopolization of devices were used ten roundabouts, being five in São José do Rio Preto and five in San Carlos, and proposed a confrontation of technical concepts between experts in the fields of Urban Planning and Urban Engineering, through AHP method, specialized literature and reality found in loco, to check for possible similarities and diferences existing between definitions, concepts and options and thus identify which factors are taken into consideration in the project, implementation and maintenance of or devices. Came to the conclusion that the specialized literature and subject matter experts defend pedestrians as a priority for the project, deployment, infrastructure and maintenance, but the devices are not able to safety.
Keywords: Engenharia de tráfego; Rotífero; Pedestres; Vias urbanas; Rotatórias; Geometria de vias; Roundabouts; Pedestrians; Traffic engineering; Geometry elements; Urban roads; ENGENHARIAS